Ratusz – archiwum pamięci - Noga, Zdzisław (Roczniki Dziejów Społecznych i Gospodarczych, 2014)
Town hall – an archive of memories (Summary) The town hall was an archive of collective memories of the town’s community and individual memories of the townspeople. It was where the most important documents for the municipality were kept, above all the foundation charter, trading privileges, as well as customs exemptions. The most important documents were read out during the annual council nominations. The town’s history thus invoked became an element of the present. Along with the development of a pragmatic approach to recording information, the town hall also became a place where individual memories were safeguarded. Towards the end of the Middle Ages, the municipal authorities sought to have the more important transactions declared before the municipal authorities and confirmed in writing. The town’s books, due to their contents which related to the whole communitatis, as well as individual citizens, were already then perceived as “monumenta of the town’s memories”. In addition to deeds and documents, other symbols and attributes of the town were kept in town halls, including seals, measures and sometimes even the town scales. Old measures, which ceased to be binding, were guarded like the new ones, outdated decrees and resolutions were also part of the town’s legal order. The town hall, and in particular the chancellery, which was usually located therein, served above all as the archive for the memories of the whole municipality and its living inhabitants – those necessary for current purposes and for dealing with current matters. At times the chancellery also served as an archive for historical memories, and was used to constantly build up and strengthen the collective identity of the townspeople.